Effect of lithium chloride additive on forward osmosis membranes performance - Nidal Hilal (Journal of Water Process Engineering, 2020)
The research efforts on the development of ideal forward osmosis membranes with high water flux and low reverse salt flux have been devoted in the recent years. In this study, thin film composite polyamide forward osmosis membranes were prepared. The porous polysulfone (PSU), polyphenylsulfone (PPSU), and polyethersulfone (PESU) substrates used in this study were prepared by the phase inversion process, and the active rejection layer was prepared by interfacial polymerization. All the membranes showed highly asymmetric porous structures with a top dense upper layers and finger-like porous substrates with macro voids in the bottom layer. The addition of 3 % lithium chloride (LiCl) to the membrane substrates resulted in an increase in both the water flux and reverse salt flux. PSU and PESU showed the highest water flux when the active layer faced the feed solution (AL-FS), while the largest water flux was obtained when the active layer faced the draw solution (AL-DS). For all the membranes, the water flux under the AL-DS orientation was higher than that under the AL-FS orientation.